Utilization of carbide sludge and urine for sustainable biocement production - Yang, Yang (2022)
Biocement is an emerging construction material via the microbially induced calcite precipitation (MICP) process for soil improvement, which could be produced using waste materials at ambient temperature. This paper investigates the possibility to produce sustainable biocement using industrial waste carbide sludge and urine. Urine was used as the growth medium for the cultivation of urease-producing bacteria (UPB). It was also used to provide urea to activate the MICP procedure together with the soluble calcium ions from carbide sludge and UPB to form calcium carbonate precipitation. The UPB produced in this way was urease active, capable of hydrolyzing urine-contained urea for calcium carbonate precipitation. The sand treated with biocement using the above ingredients achieved an unconfined compression strength of 1.2-1.7 MPa at 7.3-7.7% calcium carbonate content, whereas the permeability was reduced by two orders of magnitude. These results show the potential to use carbide sludge and urine for sustainable production of biocement.